Photosynthetic performance of Chlamydopodium (Chlorophyta) cultures grown in outdoor bioreactors - Masojídek, Jiří; Štěrbová, Karolína; Serrano, Cintia Gómez; da Silva, Jaqueline Carmo; Grivalský, Tomáš; Figueroa, Félix Lopez; Fernández, Francisco Gabriel Acién (Applied microbiology and biotechnology, 2023)
The microalga Chlamydopodium fusiforme MACC-430 was cultured in two types of outdoor pilot cultivation units-a thin-layer cascade (TLC) and a raceway pond (RWP) placed in a greenhouse. This case study aimed to test their potential suitability for cultivation scale-up to produce biomass for agriculture purposes (e.g., as biofertilizer or biostimulant). The culture response to the alteration of environmental conditions was evaluated in "exemplary" situations of good and bad weather conditions using several photosynthesis measuring techniques, namely oxygen production, and chlorophyll (Chl) fluorescence. Validation of their suitability for online monitoring in large-scale plants has been one of the objectives of the trials. Both techniques were found fast and robust reliable to monitor microalgae activity in large-scale cultivation units. In both bioreactors, Chlamydopodium cultures grew well in the semi-continuous regime using daily dilution (0.20-0.25 day-1). The biomass productivity calculated per volume was significantly (about 5 times) higher in the RWPs compared to the TLCs. The measured photosynthesis variables showed that the build-up of dissolved oxygen concentration in the TLC was higher, up to 125-150% of saturation (%sat) as compared to the RWP (102-104%sat). As only ambient CO2 was available, its shortage was indicated by a pH increase due to photosynthetic activity in the thin-layer bioreactor at higher irradiance intensities. In this setup, the RWP was considered more suitable for scale-up due to higher areal productivity, lower construction and maintenance costs, the smaller land area required to maintain large culture volumes, as well as lower carbon depletion and dissolved oxygen build-up. KEY POINTS: • Chlamydopodium was grown in both raceways and thin-layer cascades in pilot-scale. • Various photosynthesis techniques were validated for growth monitoring. • In general, raceway ponds were evaluated as more suitable for cultivation scale-up.
Keywords: Chlorophyceae; kyslík; Chlamydopodium; Microalga; bioreaktory; Oxygen; Biomass; Photosynthesis; Oxygen production; mikrořasy; Bioreactors; Microalgae; Pilot-scale bioreactors; fotosyntéza; Chlorophyll fluorescence; biomasa; Chlorophyta